Comparative mRNA and LncRNA Analysis of the Molecular Mechanisms Associated With Low Silk Production in Bombyx mori - Ruan, Jinghua; Wu, Meiyu; Ye, Xiaogang; Zhao, Shuo; Liang, Jianshe; Ye, Lupeng; You, Zhengying; Zhong, Boxiong (Frontiers in Genetics, 2021)
Naked pupa sericin and Naked pupa are two mutant strains of Bombyx mori with extremely low or no fibroin production compared to the Qiufeng and Baiyu strains, both of which exhibit very high silk fibroin production. However, the molecular mechanisms by which long noncoding RNAs regulate fibroin synthesis need further study. In this study, we performed high-throughput RNA-seq to investigate lncRNA and mRNA expression profiles in the posterior silk gland of Qiufeng, Baiyu, Nd-sD, and Nd silkworms at the third day of the 5th instar. Our efforts yielded 26,767 novel lncRNAs and 6009 novel mRNAs, the expression levels of silk protein genes and silk gland transcription factors were decreased in Qiufeng vs. Nd-sD and Qiufeng vs. Nd, while those of many genes related to autophagy, apoptosis, RNA degradation, ubiquitin-mediated proteolysis and heat shock proteins were increased. Moreover, the expression of a large number of genes responsible for protein synthesis and secretion was significantly decreased in Nd. GO and KEGG analysis results showed that nucleotide excision repair, mRNA surveillance pathways, amino acid degradation, protein digestion and absorption, ER-associated degradation and proteasome pathways were significantly enriched for the Qiufeng vs. Nd-sD and Qiufeng vs. Nd comparisons. In conclusion, our findings contribute to the lncRNA and mRNA database of Bombyx mori, and the identified differentially expressed mRNAs and lncRNAs help to reveal the molecular mechanisms of low silk production in Nd-sD and Nd, providing new insights for improvement of silk yield and elucidation of silk mechanical properties.